Benchmarking a country for efficiency improvement: A DEA-based approach - Supriyo Das; Amit Kundu (Journal of Global Entrepreneurship Research, 2019)
The purpose of this study is to determine the critical factors of environment which influence the overall performance of Micro-Small-Medium Enterprises (MSMEs). This may be conjectured that the entry and exit from small and medium industries in any country are determined by the overall environmental mapping which is explicitly reflected through several parameters such as personality of entrepreneurs and operating environment of entrepreneurs. Accordingly, revisiting these two parameters can lead a country towards sustainable development. To develop a country's efficiency in terms of its SME development, it is essential to formulate an effective policy framework. For this, it is essential to visualize the overall situation in a comparative way. Benchmarking a similar country can lead towards effective policy formulation considering that the countries belong to the same category. The present study has developed an efficiency score for each country in terms of interaction variable. This score not only makes a country fit in a position of total entrepreneurship development but also with the help of benchmarking technique, the particular country can choose another efficient country to follow. This is also very much effective in the time of policymaking. In this research, three outputs have been taken to capture the overall entrepreneurial situation and in case of input only relevant variables have been taken into consideration.
Keywords: 650; Entrepreneurial efficiency; DEA; Micro-Small-Medium Enterprises; Benchmarking; India; Developing country